2016
DOI: 10.3847/0004-637x/817/1/12
|View full text |Cite
|
Sign up to set email alerts
|

A Global Galactic Dynamo With a Corona Constrained by Relative Helicity

Abstract: We present a model for a global axisymmetric turbulent dynamo operating in a galaxy with a corona that treats the parameters of turbulence driven by supernovae and by magneto-rotational instability under a common formalism. The nonlinear quenching of the dynamo is alleviated by the inclusion of small-scale advective and diffusive magnetic helicity fluxes, which allow the gauge-invariant magnetic helicity to be transferred outside the disk and consequently to build up a corona during the course of dynamo action… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…We separately studied the influence of differential rotation on the mean field dynamo solutions as a function of the SN input rate and the rotation period when these quantities are taken to be independent and also when they are proportional to each other. The latter would be expected from correlations of the SN rate with the star formation rate and in turn, the galactic surface density and rotation rate (Prasad & Mangalam 2016).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We separately studied the influence of differential rotation on the mean field dynamo solutions as a function of the SN input rate and the rotation period when these quantities are taken to be independent and also when they are proportional to each other. The latter would be expected from correlations of the SN rate with the star formation rate and in turn, the galactic surface density and rotation rate (Prasad & Mangalam 2016).…”
Section: Discussionmentioning
confidence: 93%
“…In the cases considered above, we have assumed that the eddy time and the rotation periods are independent but in practice, models of star formation rates (SFR) in galaxies both depend on radius. We now suppose that τ ed varies with the radial coordinate r according the the prescription adopted by Prasad & Mangalam (2016). Specifically, we adopt the relation…”
Section: Case When Correlation Time and ω Both Depend On Rmentioning
confidence: 99%
“…Sellwood & Balbus (1999) have shown that the existence of the high H i velocity dispersion in the extra stellar disk of the spiral galaxies can be produced by extraction of the energy from galactic differential rotation through magneto-hydro dynamic turbulence. If MRI causes turbulence at large galactic radii, an associated α effect may develop, and regular fields will also be seen out to such large radii (Prasad & Mangalam, 2016). A much larger sample size than discussed above will help to confirm such a conclusion.…”
Section: Comparison Of Disk Magnetic Fields Observations With Theoretmentioning
confidence: 87%
“…Mean field models with helicity fluxes can avoid catastrophic quenching of the dynamo, and the simplest example of such a flux arises from advection of the field through galactic outflows (Shukurov et al, 2006b). In the case of quasi-linear dynamo model (Prasad & Mangalam, 2016), a global axisymmetric turbulent dynamo operates in a galaxy with a corona. It treats the supernovae (SNe) and magneto-rotational instability (MRI) driven turbulence parameters under a common formalism where the diffusivity and alpha effect have radial variation as the shear.…”
Section: Probing Magnetic Fields At High Redshiftsmentioning
confidence: 99%
“…S1 corresponding to Table 4. 5. Preliminary calculations using the constraint of relative helicity based on the formulations given in (Prasad et al 2014;Prasad & Mangalam 2016) and applying the constrained energy minimization principle (Mangalam & Krishan 2000;Finn & Antonsen 1983;Taylor 1974) indicate that stable configurations are possible for some regions in the parameter space of {B 0 , R}. We plan a complete solution of this allowed region and test it with numerical simulations in a paper in preparation.…”
Section: Discussionmentioning
confidence: 99%